2015
DOI: 10.1007/s11606-015-3226-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Charge Display on Cost of Care and Physician Practice Behaviors: A Systematic Review

Abstract: BACKGROUND: While studies have been published in the last 30 years that examine the effect of charge display during physician decision-making, no analysis or synthesis of these studies has been conducted. OBJECTIVE: We aimed to determine the type and quality of charge display studies that have been published; to synthe-size this information in the form of a literature review. METHODS: English-language articles published between 1982 and 2013 were identified using MEDLINE, Web of Knowledge, ABI-Inform, and Acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 31 publications
2
52
0
Order By: Relevance
“…Previous research has shown cost savings among clinicians exposed to diagnostic pricing data compared to control groups, [11][12][13][14] and in all clinical cases studied with data available, this did not affect patient outcomes or satisfaction. 13 However, the availability of outcome data remains quite limited overall.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Previous research has shown cost savings among clinicians exposed to diagnostic pricing data compared to control groups, [11][12][13][14] and in all clinical cases studied with data available, this did not affect patient outcomes or satisfaction. 13 However, the availability of outcome data remains quite limited overall.…”
mentioning
confidence: 72%
“…13 However, the availability of outcome data remains quite limited overall. 11 Interestingly, in three of six clinical and simulated studies involving pricing education, the observed cost savings did not necessarily arise from reduced testing overall, but rather from substitutions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of the study by Goetz et al (2015) would have been further enhanced had the authors 1 included the economic literature on payment mechanisms and provider behaviors. [2][3][4][5] In addition, an assessment of the quality of studies included in the review would be helpful for explaining the implications of the different methodological designs used (Cross-sectional, Cohort, Case-control studies).…”
Section: N Response To the Rising Cost Of Health Care In The Unitedmentioning
confidence: 99%
“…Goetz et al 2 identified 17 articles analyzing the effect of displayed charges for both laboratory and radiology orders as well as medication choice; they concluded that charge information changed ordering and prescribing practices. These results are consistent with those found by Horn et.…”
mentioning
confidence: 99%